Comparisons of different mean airway pressure settings during high-frequency oscillation in inflammatory response to oleic acid-induced lung injury in rabbits - Koichi Ono (Dove Medical Press, 2009)
Koichi Ono1, Tomonobu Koizumi2, Rikimaru Nakagawa1, Sumiko Yoshikawa2, Tetsutarou Otagiri11Department of Anesthesiology and Resuscitation; 2First Department of Internal Medicine, Shinshu University School of Medicine, Matsumoto, JapanPurpose: The present study was designed to examine effects of different mean airway pressure (MAP) settings during high-frequency oscillation (HFO) on oxygenation and inflammatory responses to acute lung injury (ALI) in rabbits.Methods: Anesthetized rabbits were mechanically ventilated with a conventional mechanical ventilation (CMV) mode (tidal volume 6 ml/kg, inspired oxygen fraction [FIo2] of 1.0, respiratory rate [RR] of 30/min, positive end-expiratory pressure [PEEP] of 5 cmH2O). ALI was induced by intravenous administration of oleic acid (0.08 ml/kg) and the animals were randomly allocated to the following three experimental groups; animals (n = 6) ventilated using the same mode of CMV, or animals ventilated with standard MAP (MAP 10 cmH2O, n = 7), and high MAP (15 cmH2O, n = 6) settings of HFO (Hz 15). The MAP settings were calculated by the inflation limb of the pressure-volume curve during CMV.Results: HFO with a high MAP setting significantly improved the deteriorated oxygenation during oleic acid-induced ALI and reduced wet/dry ratios, neutrophil counts and interleukin-8 concentration in bronchoalveolar lavage fluid, compared to those parameters in CMV and standard MAP-HFO.Conclusions: These findings suggest that only high MAP setting during HFO could contribute to decreased lung inflammation as well as improved oxygenation during the development of ALI.Keywords: lung protective ventilation, open lung ventilation, IL-8, neutrophil